HARGA POKOK PRODUKSI AMPLANG PADA USAHA SINAR TERANG - Rina Masithoh Haryadi, Indah Indira Yanto, Titin Ruliana, (EKONOMIA, 2020)
The purpose of this study was to find out information on the difference in cost of production according to the company with the cost of production according to the full costing method and compare the cost of production based on the full costing method with the cost of production according to Sinar Terang business.The theoretical basis used in this study is cost accounting which focuses on calculating the cost of production of envelopes in Sinar Terang's business. The analysis tool used is a full costing approach that takes into account all production costs.The results showed that the calculation of the cost of envelope production according to Sinar Terang business was Rp. 79.875 while according to the full costing method, the cost of envelope production is Rp. 84.076,91. The cost of production according to Sinar Terang business is lower than the full costing method so that there is a difference of Rp. 4.201,91. The difference occurred because the Sinar Terang business did not include factory overhead costs in production costs